Mengatasi Kesenjangan Pendidikan Berbasis Maqashid Syariah (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
The purpose of this study is to explore the strategies and models of implementation of maqashid sharia in education. The context of this study focuses on educational institutions in Indonesia, considering that this country has the largest Muslim population in the world and a diverse education system. The unit of analysis used includes various components of education, namely educators, students, learning materials, learning media, and learning methods related to the implementation of maqashid sharia. The research used is a qualitative research approach, the type of which is a literature study. By using a qualitative research method or approach, the researcher conducted an analysis in a descriptive manner. The results of the study are that the five aspects of maqashid sharia, namely hifzh al-Din, hifzh al-Naf, hifzh al-'Aql, hifzh al-Nasl and hifzh al-Mal can be integrated with learning components, namely educators, students, learning materials, learning media and learning methods. The concept of Maqashid Sharia provides a strong foundation in designing an education system that is not only oriented towards academic achievement, but also pays attention to spiritual, moral, and social aspects. By applying the principles of Maqashid Syari'ah, education can be an effective means of forming individuals who are knowledgeable, faithful, and pious.